IDENTIFIKASI MISKONSEPSI HUKUM NEWTON PADA MAHASISWA CALON GURU FISIKA UNIVERSITAS CENDERAWASIH TAHUN AKADEMIK 2017/2018 - Ahmad Teguh Hervianto; Triwiyono Triwiyono; Albert Lumbu (Papua Journal of Physics Education, 2020)
A research has been carried out on the identification of Newton's Law misconceptions in FKIP UNCEN physics education students. This study aims to describe the extent of students' misconceptions on the subject of Newton's Law. This study uses a qualitative method with a diagnostic test design that is equipped with a Certainty of Response Index (CRI) model and interviews. The data source was chosen by purposive sampling. In this study, the data source was physics semester VI FKIP UNCEN students. The focus of this research is (1) identifying misconceptions that occur in physics education students at Cenderawasih University on the topic of Newton's Law. (2) describe the percentage of misconceptions of physics education students at Cenderawasih University on the topic of Newton's Law. The results showed that 35.7% of students experienced misconceptions. Students who experienced misconceptions in Newton's First Law concept were (46.7%), in Newton's Second Law concept (33.3%), and in Newton's third Law concepts (20.0%). From the results of the interview it can be concluded that the main source of the cause of the misconception comes from the students themselves.Keywords: Misconception, Newton's Law, CRI.